Integration of Metabolomics and Transcriptomics Reveals Major Metabolic Pathways and Potential Biomarkers Involved in Pulmonary Tuberculosis and Pulmonary Tuberculosis-Complicated Diabetes - Wang, Yunguang; He, Xinxin; Zheng, Danna; He, Qiang; Sun, Lifang; Jin, Juan (Microbiology spectrum, 2023)
The comorbidity of diabetes mellitus (DM) significantly increases the risk of tuberculosis infection and adverse tuberculosis treatment outcomes. Most previous studies have focused on the relationship between the effect of blood glucose control and the outcome of antituberculosis treatment in pulmonary tuberculosis (PTB) with DM (PTB_DM); however, early prediction and the underlying molecular mechanism of susceptibility to PTB infection in patients with DM remain unclear. Pulmonary tuberculosis (PTB) and diabetes mellitus (DM) are common chronic diseases that threaten human health. Patients with DM are susceptible to PTB, an important factor that aggravates the complications of diabetes. However, the molecular regulatory mechanism underlying the susceptibility of patients with DM to PTB infection remains unknown. In this study, healthy subjects, patients with primary PTB, and patients with primary PTB complicated by DM were recruited according to inclusion and exclusion criteria. Peripheral whole blood was collected, and alteration profiles and potential molecular mechanisms were further analyzed using integrated bioinformatics analysis of metabolomics and transcriptomics. Transcriptional data revealed that lipocalin 2 (LCN2), defensin alpha 1 (DEFA1), peptidoglycan recognition protein 1 (PGLYRP1), and integrin subunit alpha 2b (ITGA2B) were significantly upregulated, while chloride intracellular channel 3 (CLIC3) was significantly downregulated in the group with PTB and DM (PTB_DM) in contrast to the healthy control (HC) group. Additionally, the interleukin 17 (IL-17), phosphatidylinositol 3-kinase (PI3K)-AKT, and peroxisome proliferator-activated receptor (PPAR) signaling pathways are important for PTB infection and regulation of PTB-complicated diabetes. Metabolomic data showed that glycerophospholipid metabolism, carbon metabolism, and fat digestion and absorption processes were enriched in the differential metabolic analysis. Finally, integrated analysis of both metabolomic and transcriptomic data indicated that the NOTCH1/JAK/STAT signaling pathway is important in PTB complicated by DM. In conclusion, PTB infection altered the transcriptional and metabolic profiles of patients with DM. Metabolomic and transcriptomic changes were highly correlated in PTB patients with DM. Peripheral metabolite levels may be used as biomarkers for PTB management in patients with DM. IMPORTANCE The comorbidity of diabetes mellitus (DM) significantly increases the risk of tuberculosis infection and adverse tuberculosis treatment outcomes. Most previous studies have focused on the relationship between the effect of blood glucose control and the outcome of antituberculosis treatment in pulmonary tuberculosis (PTB) with DM (PTB_DM); however, early prediction and the underlying molecular mechanism of susceptibility to PTB infection in patients with DM remain unclear. In this study, transcriptome sequencing and untargeted metabolomics were performed to elucidate the key molecules and signaling pathways involved in PTB infection and the susceptibility of patients with diabetes to PTB. Our findings contribute to the development of vital diagnostic biomarkers for PTB or PTB_DM and provide a comprehensive understanding of molecular regulation during disease progression.